2023
DOI: 10.1002/adma.202305868
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Ruptured Wide‐Necked Aneurysms using a Microcatheter Injectable Biomaterial

Zefu Zhang,
Hassan Albadawi,
Richard J. Fowl
et al.

Abstract: Ruptured wide‐neck aneurysms (WNAs), especially in a setting of coagulopathy, are associated with significant morbidity and mortality. We show that by trapping a sub‐millimeter clinical catheter inside the aneurysm sac using a flow diverter stent (FDS), we can achieve instant hemostasis by filling the aneurysm sac using a novel biomaterial rescuing catastrophic bleeding in large animal models. Here, multiple formulations of a biomaterial comprising gelatin, nanoclay, and iohexol were developed, optimized, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…Recently, extensive research has been conducted on gelatin for the development of injectables aimed at treating hemorrhage. Gelatin has been explored as a shear-thinning, 11−15 semisolid, 16,17 and cross-linkable hydrogel. 18,19 These studies have been motivated by the various characteristics of gelatin, such as its ability to trigger clot formation, low immunogenicity, and support for cell attachment and proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, extensive research has been conducted on gelatin for the development of injectables aimed at treating hemorrhage. Gelatin has been explored as a shear-thinning, 11−15 semisolid, 16,17 and cross-linkable hydrogel. 18,19 These studies have been motivated by the various characteristics of gelatin, such as its ability to trigger clot formation, low immunogenicity, and support for cell attachment and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Among these approaches, injectables composed of gelatin and nanoclay have shown promising results in hemorrhage control and embolization. 16,17 However, it has been reported that silicate nanoplatelets can induce cytotoxicity through the generation of reactive oxygen species, damage to cell membrane interactions, and intracellular interaction mechanisms. 20 In light of these concerns, the development of extracellular matrix (ECM)-derived cross-linkable hydrogels, such as those based on modified gelatin and hyaluronic acid, has garnered attention as injectable gels due to their cytocompatibility, biological functionality, and slow degradability relative to physically cross-linked gels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation